1978
DOI: 10.1111/j.1471-0307.1978.tb02137.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Storage Temperature on Bacterial Growth and Lipolysis in Raw Milk

Abstract: The temperature at which raw milk was stored, within the range 4°‐8°C, affected the rate of growth of bacteria and the release of free fatty acids. The effects were of both statistical and practical significance and it was shown that, by maintaining milk temperatures at 4°C, a useful extension of the storage time of raw milk could be achieved. Lipolysis in stored milk was not closely related to the total concentration of psychrotrophic bacteria, but lipolytic rancidity was not observed when the psychrotroph co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
2
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 8 publications
0
7
2
1
Order By: Relevance
“…However, after 96 h a significant increase ( P < 0.001) was detected (× 49) (this factor of bacterial count increase is the result obtained by dividing the average final count by the average initial count, and expressed as antilogarithm). Results after 48 h and 96 h of incubation differ from those described for bovine milk 19,20 . According to these studies, after 48 h and 96 h of refrigerated storage at 6°C, a 1 log cycle and 3 log cycles of increase in growth were observed in the total plate count, respectively.…”
Section: Resultscontrasting
confidence: 66%
“…However, after 96 h a significant increase ( P < 0.001) was detected (× 49) (this factor of bacterial count increase is the result obtained by dividing the average final count by the average initial count, and expressed as antilogarithm). Results after 48 h and 96 h of incubation differ from those described for bovine milk 19,20 . According to these studies, after 48 h and 96 h of refrigerated storage at 6°C, a 1 log cycle and 3 log cycles of increase in growth were observed in the total plate count, respectively.…”
Section: Resultscontrasting
confidence: 66%
“…This means that only 6% of variations in lipolysis can be explained by PBC variability. According to Muir and others () and Shelley and others (), lipolytic activity was not observed when the psychrotroph count was below 5 × 10 6 to 10 7 CFU/mL (log 10 PBC between 6.7 and 7). In our study, this value was reached only during the last day storage (Figure ).…”
Section: Interrelations Between Bmscc Pbc and Lipolysismentioning
confidence: 89%
“…Vyletělová et al (2000b) studied the growth dynamics of psychrotrophic, mesophilic and psychrotrophic lytic microorganisms in cow's raw milk in relation to time and different temperatures. Muir et al (1978) reported that during cold storage at 6°C the total count of microorganisms increased by 1 log cycle after 48 hours and by 3 log cycles after 96 hours.…”
mentioning
confidence: 99%